Endosulfan pesticide dissipation and residue levels in khat and onion in a sub-humid region of Ethiopia - Sishu, F. K.; Thegaye, E. K.; Schmitter, Petra S.; Habtu, N. G.; Tilahun, Seifu A.; Steenhuis, T. S. (Springer, 2020)
Endosulfan, a mixture of a- and ß-isomers, is used by farmers in the wet and dry season for khat and onion production. Khat leaf samples were collected in farmer fields at intervals of 1 h; 1, 5, 9 and 14 d after application. The dissipation rate of a- and ß-isomers and residue level in khat were compared with residue levels in onion. The extraction was done by using Quick Easy Cheap Effective Rugged and Safe (QuEChERS) method and analyzed by Gas Chromatography – Electron Capture Detector (GC-ECD). Greater residue a- and ß-isomer endosulfan levels were found in khat compared to onion as khat leaves are sprayed repeatedly in two week. Residue levels of khat exceeded the tolerable EU limit of 0.05 mg.kg-1 for leafy vegetables and herbs. For both raw and processed onion sample a- and ßendosulfan residues level were below the tolerable of limit EU regulation for bulb vegetables (i.e. 0. 1 mg.kg-1). The mean half-life for the a-isomer of endosulfan was 3.4 d in the wet season and 3.6 d in the dry season whilst that for the ß-isomer was 5.0 d and 5.4 d respectively. Both isomers dissipated fastest in the wet season under conditions of high humidity and precipitation. The ß-isomer persisted longer and had a lower dissipation rate from plants surface compared to the a-isomer.